PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VB SD NEGERI 51 BALAI MAKAM KECAMATAN MANDAU - Henny Guslina; Syahrilfuddin Syahrilfuddin; Hamizi Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the student achievement of sains studies fifth graderes SDN 51 Balai Makam still low with average value 68,90 (with KKM 72). The purpose of this research was to improve the students achievement of the fifth graderes SDN 51 Balai Makam. With the implementation of contextual teaching and learning model. This research was an classroom action research with two cycles in second semester 2014/2015. Before implementation contextual teaching and learning model average 68,90, after implementation contextual teaching and learning model, UH I was 78,10 that improve 13,20% from before exam with average 68,90. UH II was 82,29 that improve 19,43%. Teachers activities with the implementation contextual teaching and learning model at first meeting of first cycle was 65,62% (enough category), and second meeting was 75% (good category) that improve 10 point. At second cycle, teachers activities at first meeting was 84,37% (good category) that improve 9 point from second meeting of first cycle. Second meeting of second cycle was 90,62% (verygood category) which improve 6 point. Students activities at first meeting of first cycle was 60% (enough category),and second meeting 71,87% (good category) that improve 11 point. At second cycle, students activities at first meeting was 84,37% (good category) that improve 13 point from second meeting of first cycle. Second meeting of second cycle was 93,75% (verygood category) which improve 10 point. Implementation of contextual teaching and learning model can improvet sains studies students achievement of fifth graders (VB) SDN 51 Balai MakamKey Words : Contextual Teaching And Learning, IPA Learning Outcomes